2022
DOI: 10.1021/jacs.2c04926
|View full text |Cite
|
Sign up to set email alerts
|

Main-Group Catalysts with Atomically Dispersed In Sites for Highly Efficient Oxidative Dehydrogenation

Abstract: Transition metal oxides are well-known catalysts for oxidative dehydrogenation thanks to their excellent ability to activate alkanes. However, they suffer from an inferior alkene yield due to the trade-off between the conversion and selectivity induced by more reactive alkenes than alkanes, which obscures the optimization of catalysts. Herein, we attempt to overcome this challenge by activating a selective main-group indium oxide considered to be inactive for oxidative dehydrogenation in conventional wisdom. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…The Wu group has previously reported the VO x atomic clusters could facilitate the surface oxyfunctionalization (B–O–V sites) for C–H activation . Meanwhile, the latest research found the atomically dispersed [InOH] 2+ sites could efficiently activate C–H in light alkanes . We, therefore, speculated the isolated In–O–B clusters had higher activity for activating C–H bonds of propane.…”
Section: Resultsmentioning
confidence: 96%
“…The Wu group has previously reported the VO x atomic clusters could facilitate the surface oxyfunctionalization (B–O–V sites) for C–H activation . Meanwhile, the latest research found the atomically dispersed [InOH] 2+ sites could efficiently activate C–H in light alkanes . We, therefore, speculated the isolated In–O–B clusters had higher activity for activating C–H bonds of propane.…”
Section: Resultsmentioning
confidence: 96%
“…The recent shift from petroleum-derived naphtha to shale gas feedstock greatly increases the availability of ethylene (C 2 H 4 ) and results in a gap between the supply of C 3 H 6 and rising global demand. , To alleviate the “propylene gap”, the nonoxidative dehydrogenation of propane (C 3 H 8 ) was industrialized recently by Honeywell UOP (Oleflex) and ABB Lumus (Catofin). , However, this process suffers from (1) rapid accumulation of coke, which requires frequent catalyst regeneration, and (2) high energy need due to the endothermicity of the process. , Therefore, the oxidative dehydrogenation of propane (ODHP) represents a promising alternative, with an estimated energy saving of ca. 45% due to its exothermicity, as well as the prevention of coke formation in the presence of O 2 . Transition metal oxide catalysts, such as vanadia species (VO x ), are able to activate C–H bonds in C 3 H 8 , boding well for ODHP performance. However, the partially occupied d-orbitals in transition metal oxides interact with the reactive intermediates, binding them strongly to the catalyst surface and leading to overoxidation to CO and CO 2 , limiting the selectivity of the process. ,, …”
Section: Introductionmentioning
confidence: 99%
“…SACs on molecularly defined supports are ideal targets for employing mass spectrometry techniques relying on soft ionization methods. We employed electrospray ionization mass spectrometry (ESI-MS) for the study of solubilized SACs supported on lacunary POMs such as PW 11 O 39 . When mixing equimolar amounts of Rh nitrate and PW 11 O 39 7– , we observed the quantitative formation of PW 11 O 39 Rh 1 4– in solution with seemingly complex but easily predictable cation envelopes (Figure a). As a first test example, we conducted mechanistic studies for CO oxidation by measuring the m/z values of the observed intermediates after sequential exposure to CO and O 2 .…”
Section: Sacs Supported On Molecularly Defined Oxidesmentioning
confidence: 99%
“…Single-atom catalysts (SACs) composed of atomically dispersed metal sites on support materials have sporadically been reported for various catalytic applications throughout the last century with the field seeing a rejuvenation since the report of Pt SACs active in room-temperature CO oxidation. , While SACs have shown promising catalytic activity in many classes of reactions, mostly ascribed to their unique electronic structure, highest possible metal dispersion and metal-supported interface area, SACs also hold potential in serving as model systems for the study of active sites. Determining the identity of catalytic active sites under reaction conditions could allow for the accurate study of their intrinsic activity and selectivity by experimental and computational means . Based on these insights, the rational design of catalytic materials comprising certain active sites becomes possible.…”
Section: Introductionmentioning
confidence: 99%